PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN PENDEKATAN CONTEKSTUAL TEACHING AND LEARNING (CTL)DI SEKOLAH DASAR - MARLINA, MELI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Improved result in learning student learning student learning using IPS CTL approach in primari This reserch was derived from the learning experience in social class which was not run as it was expected. In addition, the studens got low learning achievement. To deal with this problem, CTL approach was applied. The purpose of this resertch was to increase the studen’ learning achievement in Social Science. This was a Classroom Action Research. The source of the data was the learning process and the students’ learning achievement. The subject of the reserch was the teacher and the studens. The result of the reserch showed thowed that the students’ learning achievement increased from 70.45 in cycle I to 82.82 in cycle II Keywords : student learning outcomes, CTL approach